Serum pepsinogen I concentrations in peptic ulcer patients in relation to ulcer location and stage. - Tanaka, Y (1991)
To investigate the relation of the serum group I pepsinogen (PG I) concentration to the location of gastric ulcers and chronicity of peptic ulcers, ulcer patients (n = 322) were compared with endoscopically normal subjects (n = 174). The mean PG I concentration was significantly higher in male control subjects (n = 90) than in female control subjects (n = 84). In male patients with ulcers in the duodenum (n = 69), antrum (n = 34), or angulus portion (the lower third of the body; n = 83), the mean serum PG I concentration was significantly higher than in the control subjects but in patients with an ulcer in the upper body (n = 49) it was similar to control values. Men with active or healing ulcers (n = 149) showed a significantly higher serum PG I concentration than those with scarred lesions (n = 86) when the abnormality was located in either the upper body or in the angulus portion. For female patients (n = 87), the results were similar. These results suggest that serum PG I concentrations reflect the stages of activity of peptic ulcer.